Biofertilization with Azospirillum brasilense and Rhizoglomus irregulare and reduction of nitrogen fertilization in Urochloa hybrid cv. Mulatto II - Reyes, R.; González Cañizares, P. J.; Ramírez Pedroso, J. F. (Cuban Journal of Agricultural Science, 2020)
An experiment was carried out to evaluate the contribution of biofertilization to the reduction of nitrogen fertilization in Urochloa hybrid cv. Mulato II with the use of rhizobacterium Azospirillum brasilense and the arbuscular mycorrhizal fungus (AMF) Rhizoglomus irregulare. A total of three doses of nitrogen (0, 70 and 100 kg ha-1) were evaluated, alone and combined with the application of both biofertilizers, in a random block design, with factorial arrangement and four replications. For biofertilization, inocula containing A. brasilense with a concentration of 109 CFU mL-1, and R. irregulare, with a concentration of 30 spores g-1 were used. Both were applied by the seeds coating method at the time of sowing. In the case of A. brasilense, a second application was made, at a rate of 20 L ha-1 after the first cut. The grass significantly responded (P <0.01) to nitrogen fertilization. The highest yields (14.5 t ha-1), concentrations of nitrogen in biomass (16.1 g kg-1) and organic matter digestibility (64.7 %), as well as the lowest content of neutral detergent fiber (68.1 %) were obtained with the dose of 100 kg N ha-1. With the biofertilization, without the application of nitrogen, these indicators reached similar values to those registered with the addition of 100 kg N ha-1. The effect of biofertilizers was maintained for a year. It is concluded that biofertilization with A. brasilense and R. irregulare constitutes an effective alternative to reduce the use of nitrogen fertilizer in B. hybrid cv. Mulato II. Key words: rhizobacteria, arbuscular mycorrhizal, nutritional state, forage yield.